Performance of Pile Groups Subjected to Surface Explosion - Jayasinghe, Laddu Bhagya (2017)
With the increased incidence of terrorist attacks over the world in the past few decades, the importance of response of structures, including their foundation to credible blast loads has become a vital factor in structural designs. Pile foundations are used in large weight structures to transfer the loads from the superstructure above through weak compressible soil strata into deeper, stiffer soils which have capacity to carry these loads. Piles are usually used in groups and the response of a pile within a group could be different from that of a single pile because of the pile-soil-pile interactions that take place in the group. This paper presents a numerical study on the response of pile groups to surface blasts using Arbitrary Lagrangian-Eulerian technique. Blast wave propagation in soil, horizontal pile deformation and pile damage are presented to facilitate failure evaluation of piles. Effects of the number of piles and the spacing between piles within a group on their blast response are investigated. The modeling technique developed and applied in this paper and the findings provide a comprehensive understanding on the response of pile groups to ground shocks induced by a surface explosion.